(untitled) (Applied Biological Research, 2015)
The study was conducted during spring and summer seasons of 2010-2011 to examine the changes in biochemical constituents in silk gland contents and to identify the races with better growth of silk glands in various seasons. Larval weight and silk gland weight and size were significantly high in ‘SK-1’ and ‘SK-6’ and low in ‘CSR-2’ during both the seasons. The values were marginally high in spring than summer season. Biochemical contents in silk glands decreased more in summer than spring. There was no substantial variation in the expression of molecular weight of silk gland proteins in all the genotypes tested. Carbohydrate and protein contents were significantly high in race ‘SK-1’ during both the seasons but low values in race ‘CSR-2’. There was no substantial difference in the molecular weight of silk gland proteins in different breeds evaluated.